Sifat Fisik Serbuk Effervescent Ramuan Jamu Antihipertensi - Titik Lestari (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Physical Test, Effervescent Powder, Antihypertensive Herbal. Data from Basic Health Research reports that the prevalence of hypertension in Indonesia in the population aged> 18 years is 29.8% and shows that the population of Indonesia which consumes 95.60% of herbal medicine has experienced benefits in all age groups and economic status, both in rural and urban areas but its utilization so far is still limited to self-medication and has not been done in health facilities. The scientific formula for herbal medicine for antihypertension includes Apium graveolans, Centella asiatica, Orthosiphon aristatus, Curcuma domestica, Phylantus niruri, Curcuma xanthoriza and has received a certificate from the Saintification National Herbal Medicine Commission and has been proven to be safe and efficacious. The observation authors of the use of antihypertensive herbs so far in the form of decoction preparations, it is necessary to make preparations that are practical and easy to consume and are expected with different dosage forms still have the same efficacy as lowering blood pressure, one of them in effervescent powder preparation and the need physical test for powder to find out quality standards. The aim of the study was to determine the results of the physical test of effervescent powder preparations. Method: The research method is descriptive with the research sample being effervescent powder. Results: The results showed that the results of the physical test of effervescent powder of antihypertensive herbs consisting of pH was 5.1, flow velocity was 6.56, stationary angle 21°, dispersion test was 3 minute 11 second . The moisture content of effervescent powder according to the standard is 1.5% (standard less than 5%), while the organoleptic results of effervescent powder of antihypertensive herbs showed results in fine powder, light brown color, sour taste, distinctive smell of antihypertensive herbal ingredients and homogeneous powder. Conclusion: The conclusion showed that the results of the physical test of effervescent powder was in accordance with quality standards.